NILAI SEBUAH NAMA BAGI PEREMPUAN - Firman Panjaitan; Dwi Ratna Kusumaningdyah (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2021)
Gender injustice is visible in the sexual division of labor and the mention of a married woman. Generally, the personal name of a married woman will be lost, replaced by her husband's name. This replacing name shows that there is also a pattern of ordination-subordination relationships between men and women in the family. This issue will focus on the discussion in this article, aiming that gender equality can be created starting from the smallest unit in society, namely the family. Using the phenomenological method, which departs from existing facts and then analyzes them with literature studies, this article shows that a person's name refers to a person. If someone's name replaces with another name, the person's identity will be lost and replaced by a new identity based on the new name. Then, if a married woman changes her name with her husband's name, the new name will lose her individuality. The results show that gender education has been carried out by each family through small things, especially in instilling the value of a personal name for a woman so that this will be a force to develop gender justice in society.